The Importance of English Language Learning in Early Grades: Theoretical Review and Implementation Strategies - Musinovna, Sotvaldieva Hilola (International Education Trend Issues, 2025)
This article examines the urgency of teaching English to young learners (early grade students) in the era of globalization. Early foreign language learning is believed to provide a strong foundation for children's linguistic and cognitive development. The discussion encompasses various relevant teaching methods and strategies, emphasizing the importance of age-appropriate and interest-based approaches, as well as the integration of technology in language learning. The success of early grade English education is greatly influenced by teachers’ ability to create a positive and stimulating learning environment. This is supported by second language acquisition theories such as Krashen’s Affective Filter Hypothesis (Krashen, 1985), which highlights the importance of low-anxiety settings; the Play-Based Learning principle (Pramling Samuelsson & Asplund Carlsson, 2008), which recognizes play as a natural learning medium for children; Gardner’s Multiple Intelligences theory (Gardner, 1983), which encourages a variety of methods to accommodate different learning styles; and the development of Communicative Competence (Hymes, 1972; Canale & Swain, 1980) as the primary goal of language instruction.